Scientometric analysis of global trypanosomiasis research: 1988–2017 - Hassan, Musa Dauda; Castanha, Renata Cristina Gutierres [UNESP]; Wolfram, Dietmar (Elsevier, 2020)
Background and objectives: This study provides a longitudinal scientometric analysis of global trypanosomiasis research between 1988 and 2017 as indexed in Clarivate Analytics’ Web of Science (WoS). Contributions by researchers from different countries and continents are outlined based on publication productivity, international collaborations, citation analysis, and keyword analysis. Methods: Bibliographic records of research publications indexed by WoS were downloaded based on a broad search of related terms. The authors compared the growth of literature by continent using 5-year increments, conducted a citation and co-authorship analysis by country, and a keyword analysis by publication using the scientometric visualization software VOSviewer. Results: The trypanosomiasis research literature has seen more than a fourfold annual increase in production over the study period. Contributions by authors affiliated with European and South American countries proportionately account for the most research literature. The United States and Brazil, however, occupy central roles for citations and as national contributors to the literature. The terms ‘trypanosomiasis cruzi’ and ‘chagas disease’ have become more prominent, reflecting the regional growth of research from South America. Interpretation and conclusion: Relative contributions from regions where the disease is prevalent show mixed developments. Contributions by African authors have declined proportionately to other areas of the world. However, South American contributions have increased during the study period. The contributing countries to the literature do not necessarily represent regions in which the diseases are prevalent. The same is true of the citation relationships, where European and North American contributions are more frequently cited.
Keywords: Citation analysis; Collaboration; Literature growth; Scientometrics; Trypanosoma; Trypanosomiasis